Urgensi Penyimpanan Protokol Notaris secara Elektronik dalam Kaitan Cyber Notary di Indonesia - Krida Surya, M. Javana; Nazilah Maghfiroh; Nerissa Pramesti; Adetya Firnanda (LPPM Universitas Ekasakti Padang, 2024)
Notaries have obligations, one of which is to keep and maintain notary protocols. In the digital development that continues to accelerate, this then affects the notary profession or what is usually calledcyber notary, including one of them in the case of storing notary protocols to be done electronically. The aim of this research is to explore the arrangements for storing notary protocols electronically in this regardcyber notary in Indonesia as well as exploring the legal strength of electronically storing notary protocols as evidence in the field of civil law. Apart from that, the aim of this research is to explore the legal responsibility of notaries for damage to electronically stored notary protocols. This research uses a normative research type, with an approach to statutory regulations and a conceptual approach. The literature study was carried out as a collection of legal materials, using prescriptive analysis methods. Deductive logic and systematic interpretation are used as the basis for this research. The results of the research found that there are no specific regulations regarding the electronic storage of notary protocols, especially in Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notaries. This then makes its legal strength as evidence in court still doubtful. However, legal liability for damage to notary protocols stored electronically by a notary refers to existing legal arrangements, which are currently in effect, reflecting legal certainty that has not yet been realized.